Separate and combined effects of airflow and rehydration during exercise in the heat - Mora-Rodriguez, R.; Del Coso, J.; Aguado-Jimenez, R.; Estevez, E. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To determine whether airflow is required to obtain the beneficial effects of rehydration (thermoregulatory and cardiovascular) during exercise in dry heat.